Predicting acute termination and non-termination during ablation of human atrial fibrillation using quantitative indices - Kappel, Cole; Reiss, Michael; Rodrigo, Miguel; Ganesan, Prasanth; Narayan, Sanjiv M.; Rappel, Wouter-Jan (Frontiers in Physiology, 2022)
Background: Termination of atrial fibrillation (AF), the most common arrhythmia in the United States, during catheter ablation is an attractive procedural endpoint, which has been associated with improved long term outcome in some studies. It is not clear, however, whether it is possible to predict termination using clinical data. We developed and applied three quantitative indices in global multielectrode recordings of AF prior to ablation: dominant frequency (DF), spectral power index (SPI), and electrogram quality index (EQI). Methods: In N=42 persistent AF patients (65±9 years, 14% female) we collected unipolar electrograms from 64-pole baskets (Abbott, CA). We studied N=17 patients in whom AF terminated during ablation (“Term”) and N=25 in whom it did not (“Non-term”). For each index, we determined its ability to predict ablation by computing receiver operating characteristic (ROC) and calculated the area under the curve (AUC). Results: The average DF did not differ for Term and Non-term patients at 5.28±0.82 Hz and 5.51±0.81 Hz, respectively (p=0.34). Conversely, the SPI for these two groups was 0.83±0.13 and 0.95±0.05 (p<0.001) and the EQI was 0.62±0.05 and 0.57±0.03 (p<0.0001). The AUC for predicting AF termination for the SPI was 0.85 ([0.70, 0.95] 95% CI), and for the EQI, 0.86 ([0.70,0.94] 95% CI). Conclusions: Both the EQI and the SPI may provide a useful clinical tool to predict procedural ablation outcome in persistent AF patients. Future studies are required to identify which physiological features of AF are revealed by these indices and hence linked to AF termination or non-termination.